Background color dependent photonic multilayer films for anti-counterfeiting labeling. Issue 14 (23rd March 2022) - Kim, Jeong Min; Bak, Jae Min; Lim, Bogyu; Jung, Yu Jin; Park, Byong Chon; Park, Min Ji; Park, Jong Mok; Lee, Hyung-il; Jung, Seo-Hyun
Abstract : We report a color tunable background-dependent one-dimensional photonic film according to the humidity of human breath for anti-counterfeiting labels. Abstract : A new concept for anti-counterfeiting security films that utilize the humidity from human breath to reveal a QR code on color-tunable one-dimensional (1D) PC films is presented. The 1D PC film was fabricated on a transparent polyethylene terephthalate (PET) substrate via sequential alternate layer deposition of photo-crosslinkable poly(2-vinylnaphthalene- co -benzophenone acrylate) (P(2VN- co -BPA)) and quaternized poly(4-vinylpyridine- co -benzophenone acrylate) (P(4VP- co -BPA)) (P4QP-51%). The films exhibited remarkable color transitions with reliable reversibility and reproducibility. Films placed on a black background exhibited the full visible spectrum color in a high humidity environment. Additionally, films placed on a white background displayed three different composite colors, including yellow, magenta, and cyan. These films with vivid color transitions in a high humidity environment can be applied as anti-counterfeiting films. A hidden QR code was also laser printed on the initial PC film to enhance the film's anti-counterfeiting security capabilities. These colorimetric 1D PC films can be used as anti-counterfeiting labels and for information storage.